EKSISTENSI HUKUM ISLAM DAN HUKUM ADAT DALAM SISTEM HUKUM NASIONAL - Abdurrahman Konoras (Jurnal Ilmiah Al-Syir'ah, 2016)
Islamic Law and Customary Law is part of the national legal system in addition to some other legal systems that also give meaning and role. But as a system and legal system, Islamic Law and Customary Law show a clear separation.Thus, both are standing alone and independent. The continuing development of both shows which of them can continue to exist and which of them is increasingly left behind or even reduced in terms of role.